2016
DOI: 10.1634/theoncologist.2015-0353
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT and MRI for Evaluation of Pathologic Response to Neoadjuvant Chemotherapy in Patients With Breast Cancer: A Meta-Analysis of Diagnostic Accuracy Studies

Abstract: Introduction. This study compared the diagnostic test accuracy of magnetic resonance imaging (MRI) with that of 18 F-fluoro-2-glucose-positron emission tomography/ computed tomography (FDG-PET/CT) imaging in assessment of response to neoadjuvant chemotherapy (NAC) in breast cancer. Methods. A systematic search was performed in PubMed and EMBASE (last updated in June 2015). Studies investigating the performance of MRI and FDG-PET or FDG-PET/CT imaging during or after completion of NAC in patients with histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
334
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(336 citation statements)
references
References 36 publications
1
334
0
1
Order By: Relevance
“…In a metaanalysis, Wang et al found that the accuracy of PET was greater when performed early (after 1-2 cycles of chemotherapy) rather than late. Another recent meta-analysis 10 of studies comparing FDG-PET to DCE-MRI showed that PET outperformed MRI in assessing early treatment response, with similar sensitivity, but higher specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In a metaanalysis, Wang et al found that the accuracy of PET was greater when performed early (after 1-2 cycles of chemotherapy) rather than late. Another recent meta-analysis 10 of studies comparing FDG-PET to DCE-MRI showed that PET outperformed MRI in assessing early treatment response, with similar sensitivity, but higher specificity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MRI had better performance when either of the two methods was used after the completion of neoadjuvant treatment, with significantly higher sensitivity (88% vs 57%) (19). There is a wide range of sensitivity and specificity across studies, which may be attributed to the heterogeneity between studies (17).…”
Section: Histological Examinationmentioning
confidence: 98%
“…On the other hand, FDG-PET has been shown to have low sensitivity for small lesions (13). To date, several studies examined the role of PET/CT in predicting response to neoadjuvant chemotherapy when performed after the completion of neoadjuvant chemotherapy and before surgery, with inconsistent findings, most of them comparing the findings with that of MRI (6,(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…One showed that PET was more sensitive and MRI more specific to predict pCR (7). The second showed that PET performed during NAC outperformed MRI with higher specificity (0.69 vs. 0.42) and fairly similar pooled sensitivity (0.91 vs. 0.89) (8). Despite the relatively high sensitivity, interim PET/CT in breast cancer has not yet gained a wide audience, as opposed to other similar settings in diseases such as Hodgkin disease and aggressive non-Hodgkin lymphomas (9).…”
mentioning
confidence: 98%
“…Four metaanalyses have been published in the last few years, showing a sensitivity for 18 F-FDG PET imaging close to 80%-85% and a little less specificity (3)(4)(5)(6). Two other metaanalyses compared PET with MRI (7,8). One showed that PET was more sensitive and MRI more specific to predict pCR (7).…”
mentioning
confidence: 99%